ISLAMIC WEALTH MANAGEMENT: STRATEGIES IN SHARIA-BASED FINANCIAL PLANNING AND MANAGEMENT - Risanda A Budiantoro; Amalia Nur Chasanah; Nur Rachmat Arifin; Tamimah Tamimah (Univeristas Islam Bandung, 2021)
The research aims to formulate and implement proper wealth management based on Sharia, so, it can help in achieving individual goals in financial management. Qualitative research approaches are used with consideration of low awareness in financial planning, so, it requires in-depth analysis in the formulation and implementation of sharia-based wealth management in order to be more realistic. As a form of implementation of maqasid syariah to achieve falah in the world and the hereafter. The results of this study are the utilization of Islamic wealth management on financial planning, starting from the stages of planning, implementation, supervision and evaluation of plans, to ensure the wealth will yield the benefit in the world and in the hereafter.